Marine pseudovibrio sp. as a novel source of antimicrobials - Crowley, S.; O'Gara, Fergal; O'Sullivan, O.; Cotter, P.; Dobson, A. (MDPI AG, 2014)
Antibiotic resistance among pathogenic microorganisms is becoming ever more common. Unfortunately, the development of new antibiotics which may combat resistance has decreased. Recently, however the oceans and the marine animals that reside there have received increased attention as a potential source for natural product discovery. Many marine eukaryotes interact and form close associations with microorganisms that inhabit their surfaces, many of which can inhibit the attachment, growth or survival of competitor species. It is the bioactive compounds responsible for the inhibition that is of interest to researchers on the hunt for novel bioactives. The genus Pseudovibrio has been repeatedly identified from the bacterial communities isolated from marine surfaces. In addition, antimicrobial activity assays have demonstrated significant antimicrobial producing capabilities throughout the genus. This review will describe the potency, spectrum and possible novelty of the compounds produced by these bacteria, while highlighting the capacity for this genus to produce natural antimicrobial compounds which could be employed to control undesirable bacteria in the healthcare and food production sectors.